Funicular shaping method in the iterative design of reinforced concrete arches with variable cross-section in urban areas - Stęplowski, Tomasz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This article presents the application of the funicular design method in an iterative process for reinforced concrete arches with variable cross-sections in urban environments. The study aimed to develop an optimal arch shape through multi-criteria optimization that minimizes tensile stresses, structural deflections and material volume. The geometry adapts to the internal force flow by aligning the spatial configuration and ensuring structural efficiency. The method builds on Hooke’s observation: “As hangs the flexible line, so, but inverted, will stand the rigid arch”. It is further supported by nonlinear numerical analysis conducted using the finite element method that considers second-order effects, creep, concrete shrinkage and geometric imperfections. The results show that the designed arch requires only structural reinforcement, confirming the method’s effectiveness. Various modes of arch stability loss were also evaluated. Such structures are commonly used in urban environments, serving both functional and aesthetic purposes. In the context of rapidly developing cities, this article emphasizes the role of digital transformation in structural design. It presents how graphic statics can be integrated with advanced computational tools to streamline workflows and enhance the design process.